Effect of Continuous Contour Trenches on Growth of Tree Species - Manjare, M.R.; Jadhav, N.A.; Ghule, S.T. (Indian Journal of Agroforestry, 2020)
Multipurpose trees have good potential to increase the productivity of such land in the form of various agroforestry systems. To bring the hilly sloppy area (one form of wasteland) under tree plantation, there is a need to follow soil and water treatment measures for establishment and growth of trees. There are various soil and water conservation methods, amongst these, continuous contour trenches (CCTs) offers a great promise in soil and water conservation and also for survival and growth of tree species. The technique of CCTs consists of opening of continuous trenches of 0.60 m x 0.30 m size along the contour line and again filling the opened trenches with in situ soil to the height of 70 to 100 cm. Distance between two trenches to be followed, depends upon the slope of land. The present investigation was carried out at AICRP on Agroforestry, Mahatma Phule Krishi Vidyapeeth, Rahuri during the year 1998- 99. For undertaking the experiment, 120 m x 40 m sloppy area was selected and divided into equal parts vertically for under laying two treatments viz. (1) continues contour trenches and (2) conventional pit methods. It was observed that the tree species under this study exhibited significant performance for the growth parameters like plant height and collar diameter in CCTs as compared to conventional pit method of plantation. The good performance of tree species in CCTs may be due to more moisture availability for growth and better soil profile arised due to the treatment. The present method (CCTs) has added advantage of creating good soil profile for tree establishment and development in addition to usual soil and water conservation.